La enseñanza universitaria en la carrera de arquitectura de la tecnología de construcción con tierra cruda - una experiencia chilena - Pereira Gigogne, Hugo (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2003)
The present paper contains de experience of teaching earth building architecture and construction for students of schools of architecture at the city of Santiago of Chile since 1993 .The character of the course , objectives , pedagogical methods and contains are the result of the cooperation of traditional architecture , practical and field teaching building construction prototypes and parts of buildings by the students themselves .Very important to the positive result of these courses has been the information that came from CYTED program , specifically net HABITERRA since 1990 until year 2000 and now PROTERRA project from the same program .